Energy efficiency and optimization of buildings for sustainable development in Malaysia - Revichandran, Rajeanderan; Syed Mohamed Ali, Jaffar; Idres, Moumen; Mohiuddin, A.K.M (Penerbit Akademia Baru, 2022)
Energy is the core requirement for all sectors to operate efficiently and successfully. Many sectors in Malaysia progressively uses more energy as its economy grows rapidly. The main four energy expending sectors are Industry, transportation, business and private structures. Decisively, business and private structures contribute about one third of its whole energy utilization. Corresponding to high energy utilization in Malaysia, Building Energy Efficiency (BEE) has been pulling in progressively added enthusiastically by the government of Malaysia. At present state the main difficulties faced by the organizations to achieve the BEE target are due to design restrictions of the constructions and financial obstacles that are faced by the developers. To overcome such obstacles solid energy saving tactics are in reach if early preventions are engaged, that may allow Malaysian government to progress with social and financial development in the next 50 years to come while guaranteeing the energy supply and upgrading nations territorial and global ecological standards. The particular ideal energy prospects won't happen with the current approach of Malaysian government. Recognizing the flaws and barriers met under earlier initiatives, the Malaysian government launched National Energy Efficiency Action Plan (NEEAP). These activities brought out by the government, thus to ensure the sustainability of the future energy framework of BEE. As highlighted the Malaysian government must focus monitoring on compliance and requirements of the BEE, thus to ensure the sustainability of the future energy framework. This paper uncovers the advancement and current situation of BEE in Malaysia, highlights its focus issues, and propose recommendation for its development which includes choices to improve the energy frameworks designed for better overall maintenance.